Pelos caminhos que me formei: pesquisa autobiográfica sobre a vida na periferia de São Paulo - Santos, Rubens Paulo (2018)
I am a son of the public school, from the lower classes. I was, for some time, part of the failure and dropout rates of the late 1980s and early 1990s, however, I escaped the statistics of that time that pointed out that school failure reached (and still affects) a large part of the individuals who belong to the less favored classes. This work bets on the importance of biography to understand how individuals trace their paths, give meaning to their experiences and shape their subjective constitution processes. In this perspective it proposes as its main objective: to elaborate a documentary that portrays the social mobility and improbable trajectory of a music teacher from the Elementary School. For this, it is guided by the (auto) biographical research described, among others, by Marie Christine Josso, Gaston Pineau, Maria da Conceição Passeggi. Upon completing the work, I realize that, when narrating my trajectory, I was no longer as a spectator, but as the author of my story. During the course of the documentary's construction, I experienced sensitive listening and through different dialogues I appropriated the notion of emancipation that translates as man's ability to admire, operate and transform the world, not only in him, but with him. This movement triggered a reflexive process that culminated in a process of self-training that made me return to school more clearly about my professional choices and more committed to a liberating practice.